A Transnational Research Collaboration: A Social Network Analysis and Perspectives on Our Community of Practice. Issue 4 (2nd October 2021) - Ward, Phillip; Devrilmez, Erhan; Ayvazo, Shiri; Dervent, Fatih; He, Yaohui; Iserbyt, Peter; Ince, Levent; Kim, Insook; Ko, Bomna; Li, Weidong; Tsuda, Emi
ABSTRACT: Transnational research involves research in one country that benefits that country, and where the findings are compared to the extant studies in the larger field. It also involves the search for common effects and situational influences (i.e., country and culture-specific) toward a particular research topic. In this study we examine the transnational collaboration among 11 (5 female and 6 male) researchers located in five countries conducting research in seven countries for the past 18 years. Our purpose is to elucidate relationships among the team members. First, we use social network analysis to examine our publishing and presentation productivity. Second, we use a community of practice framework to understand our collaboration and scholarly relationships. Social network analysis showed that we are a strong decentralized social network with work shared across all members. Our community of practice analysis highlighted shared values, our shared impact, professional and personal rewards and challenges.